2015
DOI: 10.1002/jclp.22174
|View full text |Cite
|
Sign up to set email alerts
|

Nonsuicidal Self‐Injury and Affect Regulation: Recent Findings From Experimental and Ecological Momentary Assessment Studies and Future Directions

Abstract: We discuss findings within the context of two central theories (i.e., opponent-process theory and distraction theory) and offer several recommendations for future research in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 48 publications
1
30
0
2
Order By: Relevance
“…Prior research suggests that both NSSI and ED behaviors serve to regulate emotion. Negative affect typically precedes NSSI, and the most common outcomes of NSSI include reducing distress and achieving relief [21][22][23]25,[30][31][32]. Negative mood is similarly hypothesized to trigger dysregulated eating and compensatory behaviors, and people generally report reduced negative affect following episodes of ED behaviors, e.g., [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research suggests that both NSSI and ED behaviors serve to regulate emotion. Negative affect typically precedes NSSI, and the most common outcomes of NSSI include reducing distress and achieving relief [21][22][23]25,[30][31][32]. Negative mood is similarly hypothesized to trigger dysregulated eating and compensatory behaviors, and people generally report reduced negative affect following episodes of ED behaviors, e.g., [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…2020, 10, 104 2 of 17 of diverse self-injurious behaviors [12][13][14][15][16] and a putative non-specific marker of general vulnerability for psychopathology [17,18]. Consistent with this notion, the most commonly reported function of NSSI and ED behaviors is to reduce negative affect [19][20][21][22][23][24][25]. Ecological momentary assessment corroborates the idea that direct and indirect self-injury are both motivated by a desire to alleviate unpleasant emotional states, as increased negative affect proximally predicts episodes of NSSI, dysregulated eating, and compensatory behaviors [26][27][28][29][30][31][32].Much like emotion dysregulation, impulsivity is implicated in various psychiatric disorders and self-injurious behaviors.…”
mentioning
confidence: 93%
“…Studies using economical momentary assessment (EMA) have shown increased feelings of loneliness, sadness, and feeling overwhelmed before engaging in NSSI [59]. In a systematic review, Hamza and Willoughby [60] found the administration of physical pain to be associated with a decrease in negative affect in all studies.…”
Section: Functions Of Nssimentioning
confidence: 99%
“…Emotion dysregulation has received considerable attention as a risk factor and correlate of NSSI (Hamza & Willoughby, ; Klonsky, ; Klonsky, Glenn, Styler, Olino, & Washburn, ). Several theories posit that emotion dysregulation and emotion deficits lie at the core of NSSI.…”
Section: Emotion Skill Deficits and Nssimentioning
confidence: 99%